2001
DOI: 10.1210/jcem.86.10.7928
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle PGF2αand PGE2in Response to Eccentric Resistance Exercise: Influence of Ibuprofen and Acetaminophen

Abstract: PGs have been shown to modulate skeletal muscle protein metabolism as well as inflammation and pain. In nonskeletal muscle tissues, the over the counter analgesic drugs ibuprofen and acetaminophen function through suppression of PG synthesis. We previously reported that ibuprofen and acetaminophen inhibit the normal increase in skeletal muscle protein synthesis after high intensity eccentric resistance exercise. The current study examined skeletal muscle PG levels in the same subjects to further investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
18
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…Similarly, Tsai et al noted that 72 h of IBU treatment does not affect mRNA or protein expression of COL1A1 and COL3A1 in cell culture (26). Given that APAP has been shown to share peripheral targets with nonsteroidal anti-inflammatory drugs like IBU (14,23), these cell culture findings are consistent with our findings where collagen mRNA expression was unchanged with analgesics. Surprisingly, we also did not observe an increase in collagen mRNA expression with acute RE even though others have noted a robust increase in skeletal muscle collagen synthesis with acute exercise (19).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, Tsai et al noted that 72 h of IBU treatment does not affect mRNA or protein expression of COL1A1 and COL3A1 in cell culture (26). Given that APAP has been shown to share peripheral targets with nonsteroidal anti-inflammatory drugs like IBU (14,23), these cell culture findings are consistent with our findings where collagen mRNA expression was unchanged with analgesics. Surprisingly, we also did not observe an increase in collagen mRNA expression with acute RE even though others have noted a robust increase in skeletal muscle collagen synthesis with acute exercise (19).…”
Section: Discussionsupporting
confidence: 91%
“…It is commonly thought that APAP produces its analgesic effect via the central nervous system. Despite this, APAP has displayed an ability to inhibit, in peripheral tissues, cyclooxygenase (COX), an upstream enzyme responsible for the production of products known to modulate pain and inflammation (14,23). Several studies have also provided convincing evidence that APAP alters cellular signaling and exercise-induced adaptions in skeletal muscle and tendon (4 -6, 11, 22, 30 -32), including reducing skeletal muscle collagen and cross-linking content (6).…”
mentioning
confidence: 99%
“…graded blockade; prostaglandin E2; inflammation; eccentric exercise PROSTAGLANDINS (PGS) ARE KNOWN TO be involved in the regulation of local blood flow within human skeletal muscles during exercise (1,16), and the concentrations of circulating proinflammatory cytokines (12) and PGs (17) are found to increase locally as well as systemically in response to exercise. PGs are synthesized from arachidonic acid derived from cell membrane phospholipids by cyclooxygenase (COX) enzymes, and the systemic release of PGs can be inhibited by oral administration of COX inhibitors known as nonsteroidal anti-inflammatory drugs (NSAIDs).…”
mentioning
confidence: 99%
“…In our study, treatment with PGF2a did not significantly change myoblast proliferation and differentiation under statin treatment but PGF2a secretion initially increased under simvastatin treatment together with PGD2, another proinflammatory PG. In a clinical study, eccentric resistance exercise initially revealed high PGF2a levels in human skeletal muscle biopsy specimens 44 . PGD2 metabolites are also linked to DMD suggesting a role in muscle cell pathology 45 .…”
Section: Discussionmentioning
confidence: 99%